Issues in assessing the health risks of n‐butanol. Issue 1 (24th June 2019) - Segal, Deborah; Bale, Ambuja S.; Phillips, Linda J.; Sasso, Alan; Schlosser, Paul M.; Starkey, C.; Makris, Susan L.
Abstract: A literature review and health effects evaluation were conducted for n‐butanol, a chemical that occurs naturally in some foods, which is an intermediate in the production of butyl esters and can be used as a gasoline additive or blend. Studies evaluating n‐butyl acetate were included in the review as n‐butyl acetate is rapidly converted to n‐butanol following multiple routes of exposure. The primary n‐butanol health effects identified were developmental and nervous system endpoints. In conducting the literature review and evaluating study findings, the following observations were made: (1) developmental findings were consistently identified; (2) neurodevelopmental findings were inconsistent; (3) evidence for nervous system effects was weak; (4) comparing internal doses from oral and inhalation exposures using physiologically based pharmacokinetic models introduces uncertainties; and (5) a lack of mechanistic information for n‐butanol resulted in the reliance on mechanistic data for ethanol, which may or may not be applicable to n‐butanol. This paper presents findings from a literature review on the health effects of n‐butanol and proposes research to help reduce uncertainty that exists due to database limitations. Abstract : A literature review and health effects evaluation were conducted for n‐butanol, a chemical occurring naturally in some foods, which is an intermediate in the production of butyl esters and can be used as a gasoline additive or blend. The primary n‐butanol health effects identified were developmental and nervous system endpoints. This paper presents findings from a literature review on the health effects of n‐butanol, discusses health assessment issues and proposes research to help reduce uncertainty that exists due to database limitations.